A comparison of drought responses in wild wheat relatives and domesticated wheat grown under irrigated and rainfed field conditions - Pantha, Sumitra; Kilian, Benjamin; Özkan, Hakan; Zeibig, Frederike; Frei, Michael; Justus Liebig University Giessen (My University, 2025)
Context: Domestication and breeding processes for developing modern wheat plants from diverse wild relatives and landraces have had unintended effects of loss of genetic diversity. This reduction in genetic variation undermines the ability of modern wheat cultivars to tolerate environmental stresses such as drought. Wheat wild relatives possess untapped genetic potential for tolerating abiotic stress, especially drought. Yet, their morpho-physiological adaptation and drought stress resilience mechanisms remain underexplored. Objective: This study aimed to investigate the adaptive responses of plants within the Triticum spp. genepool, encompassing wheat wild relatives, landraces, and modern cultivars to drought stress under rainfed and irrigated field conditions. Methods: From an initial pool of 110 genotypes screened during the first growing season in 2022, 20 best performing genotypes, including modern cultivars for comparison, were selected for a second growing season in 2023 based on their relative yield performance. Two different treatment conditions, irrigated and rainfed, were applied during both growing seasons. This experiment observed single plants per replicate. Multiple parameters, including days to heading and flowering, plant height, number of spikes per plant, spike length, spike weight per plant, straw weight per plant, aboveground biomass per plant, grain yield per plant, thousand kernel weight, harvest index, stomatal conductance, and vegetation indices, were assessed on the selected genotypes. Results: Taking averages measured across both growing seasons, we observed significant genotypic variation across several parameters: days to heading and flowering, plant height, number of spikes per plant, spike length, spike and straw weight per plant, aboveground biomass per plant, grain yield per plant, thousand kernel weight, harvest index, stomatal conductance, and vegetation indices. Water stress during the rainfed treatment significantly reduced grain yield (by 21 %) and stomatal conductance (by 45 %). Stomatal conductance was associated with grain yield and yield-related traits under rainfed conditions. Diverse physiological drought tolerance mechanisms associated with stomatal regulation were identified, revealing genotype-specific responses to drought stress. Genotypes such as T. dicoccoides (G242), T. urartu (G45), T. boeoticum (G27) and T. araraticum (G221) exhibited isohydric adaptation, whereas T. monococcum sinskajae (G89) and T. durum cv. Sambadur (G41) exhibited anisohydric adaptation. Conclusion: Some genotypes of T. dicoccoides, T. urartu, T. boeoticum and T. araraticum exhibited isohydric adaptation, while T. monococcum sinskajae and T. durum cv. Sambadur exhibited anisohydric adaptation under drought stress which needs further verification. These genotypes can serve as donors for introducing drought tolerance traits within wheat improvement programs.
Keywords: ddc:630